The dynamic behaviour of a turbine rotating system - Barzdaitis, Vytautas (Strojniški vestnik, 2006)
This paper looks at the dynamics of a steam-turbine rotating system using theoretical modeling and a simulation combined with experimental condition monitoring and diagnostics results. Two rotors are connected by the toothed wheel coupling with elastic plate packets. There are thin layers of oil between the plates and the semi-couplingsć teeth. Elastic contacts can occur between the plates, the plate packets and the semi-couplings' teeth. A dynamic model of the rotating system with the toothed-wheel coupling was designed and simulated. The simulation and experimental measurement results of the rotating system were used to identify the vibration sources and the failures of the elastic plates due to fretting corrosion and the misalignment of the rotors.
Keywords: parne turbine; rotorji; dinamika; numerične metode; korozija